(untitled) (Ordia Prima, 2025)
The teaching of the Nicomachean Ethics at the University of Paris from 1230 to 1245 (there is no previous evidence of this kind of teaching although it was incorporated in the syllabi) can be studied through five commentaries transmitted in several cases by a single manuscript. Those manuscripts and the commentaries preserved by them will be presented establishing the focus on the form of transmission and grouping of texts in thematical codicological units. Five texts will be presented (1. Lectura abrincensis in Ethicam Veterem, 2. Lectura parisiensis in Ethicam Novam et Veterem, 3. Lectio cum questionibus [in Ethicam Novam], 4. Lectura cum questionibus in Ethicam Novam et Veterem, 5. Roberti Kilwardby, Sententia in Ethicam Novam et Veterem) which are witnessed by eight manuscripts of seven libraries in four European countries. Also, the challenges of their critical editions will be described and several strategies to face them will be discussed.